Analysis of Factors Affecting Public Tax Liability and Difficulties in Fulfilling Tax Obligations in Indonesia - Simangunsong, Samaria; Agustia, Mira; Fitriani, Novi; Zahara, Siti; Aliah, Nur (Educational Studies and Research Journal, 2026)
This study aims to analyze the factors that influence public tax liability and the difficulties in fulfilling tax obligations in Indonesia through a literature review approach. This study is based on various previous studies on taxpayer compliance and noncompliance, which show that psychological, social, economic, and regulatory factors play an important role in determining the amount of tax liability and the public's ability to fulfill it. Factors such as tax awareness, tax knowledge, perceptions of the fairness of the system, the effectiveness of tax services, and the complexity of tax administration have been shown to influence the level of public compliance. In addition, individual economic conditions and the level of trust in the government are also major obstacles to the payment of tax obligations. The results of the literature review show that the difficulties faced by the public generally arise due to complex regulatory changes, low tax literacy, and weak socialization from the tax authorities. This study recommends the need for broader tax education, simplification of the reporting system, and increased transparency of fiscal policies in order to reduce the burden of liabilities and increase tax compliance among the public in Indonesia.